SISTEM INFORMASI PENJUALAN OBAT-OBATAN PADA PT. SAPTA SARI TAMA JAMBI - Lucy Simorangkir (JURNAL AKADEMIKA)
The author describes the application of this scientific data processing and data reporting sales information drugs at. Sapta Tama Sari Jambi part of data processing in order to facilitate the registration of drugs sales data in the process of selling data processing and reduce the risk of recording errors and simplify report in making the report . Making Application processing sales data and sales reports on PT . Sapta Tama Sari Jambi using Visual Basic 6.0 , MySQL to manage the data and databases , as well as to create a report using Data Report . Data or information relating to this research obtained through field studies and literature . The conclusion by the authors in making this application is data recording sales of drugs and medicines sales reports can be done in a computerized , reducing the risk of mistakes in preparing reports quickly and accurately.